Could chronic opioid use be an additional risk of hepatic damage in patients with previous liver diseases, and what is the role of microbiome? - Tarantino, Giovanni; Cataldi, Mauro; Citro, Vincenzo (Frontiers in Microbiology, 2024)
Summary: Among illicit drugs, addiction from opioids and synthetic opioids is soaring in an unparalleled manner with its unacceptable amount of deaths. Apart from these extreme consequences, the liver toxicity is another important aspect that should be highlighted. Accordingly, the chronic use of these substances, of which fentanyl is the most frequently consumed, represents an additional risk of liver damage in patients with underlying chronic liver disease. These observations are drawn from various preclinical and clinical studies present in literature. Several downstream molecular events have been proposed, but recent pieces of research strengthen the hypothesis that dysbiosis of the gut microbiota is a solid mechanism inducing and worsening liver damage by both alcohol and illicit drugs. In this scenario, the gut flora modification ascribed to non-alcoholic fatty liver disease performs an additive role. Interestingly enough, HBV and HCV infections impact gut–liver axis. In the end, the authors tried to solicit the attention of operators on this major healthcare problem.